2009
DOI: 10.1039/b823149d
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent reactions for the synthesis of multifunctional agents with activity against cancer cells

Abstract: Multicomponent Passerini and Ugi reactions enable the fast and efficient synthesis of redox-active multifunctional selenium and tellurium compounds, of which some show considerable cytotoxicity against specific cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 12 publications
0
32
0
2
Order By: Relevance
“…We have already shown that the quinone containing chalcogen compounds (3, 4, 5 and 6) exert their main cytotoxic effects at least in part via modulation of the intracellular redox state. 13 Consequently, these compounds were able to inhibit cancer cell proliferation by induction of Oxidative Stress, cell cycle delay, alteration of the cytoskeleton and apoptosis. Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…We have already shown that the quinone containing chalcogen compounds (3, 4, 5 and 6) exert their main cytotoxic effects at least in part via modulation of the intracellular redox state. 13 Consequently, these compounds were able to inhibit cancer cell proliferation by induction of Oxidative Stress, cell cycle delay, alteration of the cytoskeleton and apoptosis. Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…As before, the IMCR-based approach turned out to be rather successful for the synthesis of a range of chemically diverse sulfur-, selenium-and tellurium-containing peptidomimetic compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These compounds were tested in various cancer cell lines and, in the case of the tellurium compounds, showed considerable activity in many of these cell cultures, possibly by selectively damaging the ER and actin cytoskeleton, delaying the cell cycle and inducing apoptosis.…”
Section: Resultsmentioning
confidence: 93%
“…Chalcogens (sulfur, selenium and tellurium) bearing isonitriles have therefore been synthesized accordingly to overcome this sophisticated limitation. 13 Based on these results, we are now interested to further explore the reactivity of these isonitriles and to generate a library of diverse and highly functionalized organochalcogens of expected biological activity.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
See 2 more Smart Citations